2022
DOI: 10.3390/ijms23158200
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Platform Unveils the Brain Glycogen Phosphorylase as a Potential Therapeutic Target for Glioblastoma Multiforme

Abstract: In the last few years, several efforts have been made to identify original strategies against glioblastoma multiforme (GBM): this requires a more detailed investigation of the molecular mechanism of GBM so that novel targets can be identified for new possible therapeutic agents. Here, using a combined biochemical and proteomic approach, we evaluated the ability of a blood–brain barrier-permeable 2,3-benzodiazepin-4-one, called 1g, to interfere with the activity and the expression of brain glycogen phosphorylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The results highlighted PYGB as a potential therapeutic target for U87MG of GBM and indicated that 2,3-benzodiazepin-4-one can be used to develop anti-cancer drugs for glioblastoma because it can negatively regulate glucose uptake and metabolism (the "Warburg effect") [63].…”
Section: Pygb In Glioblastoma Multiforme (Gbm)mentioning
confidence: 99%
“…The results highlighted PYGB as a potential therapeutic target for U87MG of GBM and indicated that 2,3-benzodiazepin-4-one can be used to develop anti-cancer drugs for glioblastoma because it can negatively regulate glucose uptake and metabolism (the "Warburg effect") [63].…”
Section: Pygb In Glioblastoma Multiforme (Gbm)mentioning
confidence: 99%
“…Twenty-seven molecules were mainly selected on the basis of the best binding energies obtained from the results of the MTiOpenScreen web server. To check these results, we carried out a further docking analysis using the SwissDock web server, as previously reported [38], based on the EADock DSS algorithm [39,40], and setting the docking type as accurate without a definition of the region of interest to include the whole protein in the search space. The final geometry of the complexes obtained was rendered by PyMol software (The PyMOL Molecular Graphics System, Version 2.5.2, Schrödinger, LLC., Cambridge, MA, USA), and the 3D representation of the interaction was obtained by the Protein-Ligand Interaction Profiler (PLIP) web server [41].…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Ferraro et al have characterized a novel potential therapeutic target for the treatment of glioblastoma multiforme (GBM) [17]. In their study, the authors identified brain glycogen phosphorylase (PYGB) as a valid molecular target for the treatment of GBM, which catalyzes the transformation from glycogen to glucose 1-phosphate and supports glucose metabolism in cancer cells (the so-called "Warburg effect").…”
mentioning
confidence: 99%
“…In their study, the authors identified brain glycogen phosphorylase (PYGB) as a valid molecular target for the treatment of GBM, which catalyzes the transformation from glycogen to glucose 1-phosphate and supports glucose metabolism in cancer cells (the so-called "Warburg effect"). The results of a combined biochemical and proteomic analysis revealed that PYGB could be targeted in different GBM cell lines and primary neuronal cells via 2,3-benzodiazepin-4-one, a blood-brain barrier-permeating compound, also known as 1g, that interferes with cancer cell metabolism [17].…”
mentioning
confidence: 99%